Transposition of the EU Directive 2020/1828 on Representative Actions for Consumer Collective Interests in Lithuania - Sirvydytė, Monika (Teisė, 2025)
This article examines the implementation of Directive (EU) 2020/1828 of the European Parliament and of the Council of 25 November 2020 on representative actions for the protection of collective consumer interests in Lithuania. The study highlights the Directive’s significance for the protection of collective consumer interests, analyses the legislative choices made, and critically assesses certain statutory provisions. The research reveals that the absence of a regulated and effective funding system for representative actions in the Directive reduces the potential for significant advancements in consumer collective interest protection. An assessment of the national regulation indicates a lack of thorough argumentation regarding certain procedural aspects of representative actions, as well as a missing systemic approach to civil procedure law and consumer procedural safeguards.